2021
DOI: 10.2147/ijgm.s324126
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three Potential circRNA Biomarkers of Polycystic Ovary Syndrome by Bioinformatics Analysis and Validation

Abstract: Objective It is well known that circRNAs are closely involved in the progression of various diseases. However, their functions and potential regulatory mechanisms in polycystic ovary syndrome (PCOS) remain largely unknown. In the present study, our aim was to investigate the potential diagnostic value of circRNAs in PCOS. Methods The circRNA dataset GSE145296, mRNA dataset GSE155489 and miRNA GSE138572 were downloaded from Gene Expression Omnibus (GEO) database. Then, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…PCOS patients’ impaired endometrial receptivity and reproductive outcomes may be affected by changes in numerous signal pathways as the disease progresses ( 17 , 42 , 43 ). In our study, the DEPs were shown to be involved in ferroptosis and mitochondrial dysfunction based on the KEGG pathway and subcellular location prediction system.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS patients’ impaired endometrial receptivity and reproductive outcomes may be affected by changes in numerous signal pathways as the disease progresses ( 17 , 42 , 43 ). In our study, the DEPs were shown to be involved in ferroptosis and mitochondrial dysfunction based on the KEGG pathway and subcellular location prediction system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hsa_circ_0043533 and hsa_circ_0043532 also achieved high AUC values of 0.709 and 0.718, respectively [49]. Huang et al verified that three circRNAs (hsa_circ_0085997, hsa_circ_0075692, and hsa_circ_0075691) were dysregulated in PCOS and showed significant distinguishing efficiency with AUC values from 0.75 to 0.89 [104]. These three circRNAs have not been previously reported in other diseases, implying that their specificity and effectiveness make them potential biomarkers for PCOS.…”
Section: Circular Rnas As Diagnostic Biomarkers In Pcosmentioning
confidence: 94%
“…Specifically, in GCs, the downregulation of circ_0085997 leads to PRICKLE2 inhibition, whereas upregulation of miR-346 occurs. This regulatory mechanism involving the circRNA promotes the miR-346/PRICKLE2 axis, which influences the inflammatory response during the development of polycystic ovary syndrome (PCOS) [ 50 ]. MiR-346 appears to be crucial in ER-stress-induced autophagy [ 76 ], and it promotes the LIF/STAT3 signaling pathway in Hu sheep ovarian GCs [ 77 ].…”
Section: Proven and Potential Study Of Novel Cernets In Pcosmentioning
confidence: 99%
“…Within PCOS research, ceRNETs represent a novel and promising avenue that can greatly enhance our understanding of the molecular processes driving polycystic ovarian syndrome and its pathophysiology. In this study, we conducted a comprehensive review of validated ceRNAs, including non-coding RNAs such as lncRNAs, miRNAs, and mRNAs [ 122 , 127 , 135 , 142 , 151 , 170 , 176 , 183 , 198 ] Additionally, we reviewed ceRNAs composed of circRNAs, miRNAs, and mRNAs [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Furthermore, we emphasized on role of ceRNAs associated with PCOS in rodent as animal models, encompassing lncRNAs, miRNAs, and mRNAs [ 204 , 207 ].…”
Section: Remarkable Conclusionmentioning
confidence: 99%